Mathematical model of coupled dual chemical osmosis based on mixture-coupling theory - Chen, X. (Elsevier Ltd, 2018)
Very low permeability soils and rocks can act as a semi-permeable osmotic membrane, which will generate osmotic flow. Such complexities have been extensively studied, but dual chemical osmosis, the influence of sorption on chemical osmotic flow and the consequent influence on the stress/stain change remains unclear. This study extends mixture-coupling theory, by including chemical sorption entropy and chemical potential, and provides a new-coupled formulation for chemical transport in very low permeability rock. The classical Darcy's Law and Fick's Law have been modified to include the influence of chemical potential and sorption under relevant conditions, and dual chemical osmosis. The mechanical deformation has been coupled with the water and chemical flows using Helmholtz free energy. Finally, a coupled unsaturated hydro-mechanical-chemical model which considers dual chemical osmosis and sorption is presented. This mathematical model provides the possibility of using dual chemicals to control osmotic flow and chemical transport, which leads to important engineering applications such as those in the field of nuclear waste disposal. Â© 2018 Elsevier Ltd